PENGARUH PENERAPAN GREEN ACCOUNTING, PROFITABILITAS, DAN CORPORATE SOCIAL RESPONSIBILITY TERHADAP NILAI PERUSAHAAN - Ni Komang Nilawati Astuti; Ni Luh Putu Sri Purnama Pradnyani; Putu Aristya Adi Wasita (Universitas Triatma Mulya, 2023)
The purpose of this study is to determine the effect of implementing green accounting on profitability and corporate social responsibility on company value. The research method used is quantitative research with secondary data. This research was conducted at coal subsector mining companies listed on the Indonesia Stock Exchange for the period 2019–2022. The sampling method was purposive sampling, and 33 observations were made from companies that released annual reports and sustainability reports in a row from 2019 to 2021. The data analysis technique used is multiple linear regression analysis with SPSS 26-assisted data presentation. The results of this study indicate that the applicability of green accounting has a positive influence on firm value. Profitability has a positive influence on firm value. Corporate social responsibility (CSR) has a positive influence on firm value. Based on these results, there are three factors that affect the value of the company: green accounting, profitability, and CSR. This factor is expected to be a consideration for investors when investing because an increase in company value is marked by an increase in the company's stock price, ensuring that investors get optimal profits (returns).